A Study on the Combustion Performance of Diesel Engines with O2 and CO2 Suction - Qinming Tan; Yihuai Hu; Xusheng Zhang; Hongsheng Zhang (Journal of Chemistry)
Based on the chemical reaction mechanism of fuel combustion, NOx in the diesel emissions is mainly generated from N2 inside the burning environment of engine cylinder. Taking the gas mixture, O2 and CO2, as the intake air, nitrogen-free intake is accessible, and through simulative calculations and experiments, researchers can make a study of the ignition and combustion performances of the engines. Taking a type of “4135ACa” diesel engine as the research object, the study suggested the following: in the environment of O2 and CO2, only when the volume fraction of O2 reaches 45% can the engine be ignited and kept running; engine operation became more steady after its O2 percentage increased to 50%. There is no NOx emission of engine’s nitrogen-free combustion, despite some black particles in the exhaust gas. So, the bottleneck of “NOx-Soot” emission is successfully transformed into how to optimize the combustion performance of engines. Additionally, through simulative calculations, influences of the O2 volume fraction on the nitrogen-free combustion performance have been researched; results suggested that it can help promote the burning efficiency with the increase of O2. When it reached 60%, its heat output in the cylinder has been equal to that under the operation condition of air intake. Therefore, nitrogen-free combustion can be used in some NOx control area, especially to some power plant which worked underwater. The huge gas consumption can be recycled from exhaust gas by closed cycle.